Mitochondrial DNA Sequence and Lack of Response to Anoxia in the Annual Killifish Austrofundulus limnaeus - Wagner, Josiah T.; Herrejon Chavez, Florisela; Podrabsky, Jason E. (Frontiers in Physiology, 2016)
The annual killifish Austrofundulus limnaeus inhabits ephemeral ponds in regions of Venezuela, South America. Permanent populations of A. limnaeus are maintained by production of stress-tolerant embryos that are able to persist in the desiccated sediment. Previous work has demonstrated that A. limnaeus have a remarkable ability to tolerate extended periods of anoxia and desiccating conditions. After considering temperature, A. limnaeus embryos have the highest known tolerance to anoxia when compared to any other vertebrate yet studied. Oxygen is completely essential for the process of oxidative phosphorylation by mitochondria, the intracellular organelle responsible for the majority of adenosine triphosphate production. Thus, understanding the unique properties of A. limnaeus mitochondria is of great interest. In this work, we describe the first complete mitochondrial genome (mtgenome) sequence of a single adult A. limnaeus individual and compare both coding and non-coding regions to several other closely related fish mtgenomes. Mitochondrial features were predicted using MitoAnnotator and polyadenylation sites were predicted using RNAseq mapping. To estimate the responsiveness of A. limnaeus mitochondria to anoxia treatment, we measure relative mitochondrial DNA copy number and total citrate synthase activity in both relatively anoxia-tolerant and anoxia-sensitive embryonic stages. Our cross-species comparative approach identifies unique features of ND1, ND5, ND6, and ATPase-6 that may facilitate the unique phenotype of A. limnaeus embryos. Additionally, we do not find evidence for mitochondrial degradation or biogenesis during anoxia/reoxygenation treatment in A. limnaeus embryos, suggesting that anoxia-tolerant mitochondria do not respond to anoxia in a manner similar to anoxia-sensitive mitochondria.